Nothing about me without me: why an EU health literacy strategy embracing the role of citizens and patients is needed - Alexander Roediger; Kaisa Immonen-Charalambous; Markus Kujawa; Kristine Sørensen (Archives of Public Health, 2019)
Abstract As a multi-faceted concept, health literacy concerns the capacities of people to meet the complex demands of health in a modern society, starting with basic skills and ending with active citizenship. The importance of advancing health literacy in Europe was recognised by the European Commission in various communications and initiatives and most recently by the OECD. However, a strategic approach combined with a long-term action plan is still missing. This commentary advocates for an EU strategy on health literacy to fully take into account the partnership of citizens and patients with professionals and decision-makers in health and health care to promote health literate societies.